Analysis of Road Maintenance Priorities on Provincial Roads in the UPT PJJ Malang Region Using the Analytical Hierarchy Process Based on the Provincial/District Roads Management System - Hariyadi, Slamet; Riduan, Ervinda; Tjendani, Hanie Teki (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The management of transportation infrastructure plays a vital role in supporting regional connectivity and sustainable development. However, limited government budgets often constrain the ability to maintain the entire road network, requiring a decision-making model that can objectively determine maintenance priorities. This research aims to analyze the prioritization of provincial road maintenance in the UPT PJJ Malang region using the Analytical Hierarchy Process (AHP) integrated with the Provincial/District Roads Management System (PKRMS). The study adopts a quantitative descriptive method that combines technical data from PKRMS with expert-based weighting analysis through AHP. The expected outcome is a decision-support model that can rank road segments according to their strategic, technical, and socio-economic importance. This approach not only supports transparent and efficient infrastructure management but also provides an applied learning framework for vocational engineering education, fostering smart and sustainable human resources in the field of transportation infrastructure management.